The Relation between Influenza Pandemics and Solar Activity - Karim, Laith; Abbas, Marwa (Iraqi Journal of Science, 2023)
Influenza is a highly infectious and lethal viral disease, it appears on Earth periodically in connection with the passage of comet in the vicinity of Earth around the Sun .it is believed that particles spread from the tail of the comet due to solar heating energy ,are contaminated with very tiny small particles considered as viruses. Viruses reach the Earth with the power of the solar wind due to solar activity cycle which is driven every 11 year. Viruses pushed towards Earth’s atmosphere, then precipitate on clouds and reach the surface of Earth. These viruses are very well shielded and unaffected by even UV radiation ,but the only way the shell is melt when they passes through the digestive system . Results showed a good correlation between sunspots cycles and influenza epidemics events.